(3TQM GdSfhSjIs - (3GdJdeSGfj, eMeO Hf YeQ Hf eOjf, cGf MjG (B1202 (3g`s ((3YKeGf Hf hdjs)
(3ChdgG (B:s
(3HYO GdHSedI ; jbhd YHjO Gddg JYGdi eMeO Hf YeQ Hf EHQGgje GdedGdj GdJdeSGfj GdMeO KfGA GdefaQO HhLhO GdhMOGfjI aj GdPGJ hGdUaGJ hGdCaYGd hHYO abO SCdfj HYV GdeMHjf Cf CVY dg TQMG eNJUQG Ydi age YbjOI GdTjN CHj YHO Gddg eMeO Hf jhSa GdSfhSjs
(3BNQgG (B:s
(3bGd GdTjN (B( (3QM (B) (3hJHGjfg GdJhajb dG QH ZjQg hdG jNai Ydjc MSf efGSHI OYGA GdTjN (B( (3QM (B) (3dfaSg hGMjJg HGdNJe Ydi Cced GdMGdGJ hPdc HGdfWb ajgG hGSJMVGQ GdbdH HgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3e (B3 / 567s
(3cTa GdXfhf (B1 / 170s
(3agQS GdNOjhjI (B4 / 264s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds